The Effect of Polyetherimide Polymer Membrane Composition on the Performance Efficiency of Dye Sensitized Solar Cell (DSSC) Based on Natural Photosensitizer of Butterfly Pea Flowers - Fachrirakarsie, Fadlurachman Faizal; Kusumawati, Nita (Jurnal Pijar Mipa, 2024)
Global energy consumption will grow 1.3% in 2023-2024. This raises concerns about the scarcity of energy sources, most of which come from coal. This research is a true experiment with a one-shot case study design and aims to analyze the Dye-Sensitized Solar Cell (DSSC) from butterfly pea flowers (BPF) extract. However, DSSC has significant problems with liquid electrolyte leakage and solvent evaporation. Therefore, polyetherimide (PEI) membranes were investigated to overcome this problem. The BPF extract was examined for wavelengths, producing 573 nm and 617 nm wavelengths. The band gap was also checked, and it was found to produce 0.52 eV. The membrane used has five variations, where M3 is the most stable, with a reduction in performance efficiency of only 98%. The membrane has a porous surface, asymmetric structure, and a crystallinity degree of 12.77%. Overall, this membrane shows the most optimal performance in DSSC among other membranes.